Detection of graft fibrosis by vibration‐controlled transient elastography in pediatric liver transplant recipients. (19th May 2020) - Costa, Peter; Kogan‐Liberman, Debora; Rudolph, Bryan; Silver, Ellen; Ewart, Michelle; Raizner, Aileen; Cunningham, Ryan; Ovchinsky, Nadia
Abstract: Pediatric liver transplant recipients are at risk of developing graft fibrosis which can affect patient survival. VCTE is a non‐invasive tool that measures LSM and has been shown to correlate with hepatic fibrosis. The aim of this study was to therefore evaluate the ability of LSM to predict fibrosis in pediatric liver transplant recipients with different graft types. We performed a cross‐sectional study evaluating LSM of 28 pediatric liver transplant recipients who underwent a total of 20 liver biopsies within 1 month of LSM. LSM was compared to liver histology as well as graft type: WL or PL. The median LSM of all post‐transplant patients was 5.6 kPa (range = 2.7‐18.3). There was a statistically significant correlation between LSM and METAVIR fibrosis score ( P  = .001) and LAF score ( P  < .001). There was no difference in LSM between graft type ( P  = .088). The AUROC curve for LSM predicting any significant fibrosis ( F  ≥ 2) was 0.863. A cutoff value of 7.25 had a sensitivity of 71%, specificity of 100%, NPV of 87%, and PPV of 100% for significant fibrosis. LSM by VCTE is feasible in pediatric liver transplant recipients regardless of graft type. We found a significant correlation between LSM and hepatic fibrosis and established a cutoff value that may help determine which patients warrant further evaluation for graft fibrosis.